A expressão da ética nas práticas de profissionais da saúde no contexto de unidades de internação hospitalar - Livia Cozer Montenegro (2014)
In the current context of transformations characterized by globalization, the society has experienced new ways of living, resulting from technological processes, which point to a deification of materials, individual and virtual aspects at the expense of humane and supportive personal relationships. Social changes have evolved in such a way that has allowed individuals to build more autonomous and global human relations which domain individualistic behavior, of indifference to the other and trivialization of moral values, fueling a crisis of moral order in humanity. In the health sector, the concern with feelings of indifference that pervades social relations becomes even more relevant, since health is characterized as a work of non-material sphere of production, which is completed at the time of its completion and is accomplished by means of a live act and work in a process of constant relations. In order to understand how ethics is expressed in the practice of health professionals in the context of hospital units, we carried out a qualitative research based on poststructuralist epistemology with 30 individuals from different professional categories. The search occurred in all inpatient units of medical and surgical clinic of a teaching hospital in the capital of Minas Gerais State, during the period from December 2012 to April 2013. Data collection was performed through recorded interviews, guided by a semistructured script and associated with projective technique. Data were analyzed by means of discursive textual analysis that has been revealed as a technique that tends to value subjective elements, always in the direction of the search for multiple understandings of the phenomena. These understandings have their starting point in language and in a sense that it can be established with the appreciation of the contexts and historical movements in which the senses are done. As a result, it was possible to identify five dimensions by which ethics is expressed: ethics as the product of human existence; expressions and impressions of the concept of ethics in the constitution of being a health professional; the expression of ethics in the context of health and hospital: a needs of others; expression of ethics in everyday practices of health professionals: the centrality of human relationships; ethical problems that arise in everyday practice of health professionals; and the expression of the ethical in decision of health professionals. The results showed that although health professionals present feelings of care, diligence and concern for each other, in practice the ethics is deconstructed, making their relationships very stressful and apparently satisfactory. Each professional valuesas the foundation of ethics its own uniqueness, and in the face of uncertainties, supports its decisions on concepts learned in the family. In practice, ethics is influenced by the collective work in which the web of power relationships and vanities game of intellectual capital hide its expression. Practical ethics, thus, becomes a volatile concept in the minds of professionals. We conclude that, for the professional of this study, ethics is viewed from two perspectives: the first concerns a concept related to everyday life, which represents the human professional being whose ethics is unique, real, concrete, omnipresent and dynamic. And the second relates to the job of representing the professional in its action, in which ethics is abstract, invisible and static.